2022
DOI: 10.1038/s41598-022-11008-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a web-based headache diagnosis questionnaire

Abstract: Information technology advances may help in conducting epidemiological studies using web-based surveys. Questionnaire-based headache diagnosis should be validated against the doctor’s diagnosis. This study aimed to develop and validate a web-based diagnostic questionnaire for migraine, probable migraine (PM), and tension-type headache (TTH). We constructed a seven-item questionnaire for diagnosing migraine, PM, and TTH. A web-based survey was conducted among adults aged 20–59 years; migraine, PM, and TTH were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…to diagnose migraine and assess the validity of the migraine diagnosis from the survey responses. The diagnostic sensitivity and specificity of our survey were 92.6% and 94.8%, respectively, with a kappa coefficient of 0.875 21 . Non-migraine headache was defined as any headache not fulfilling the migraine diagnostic criteria.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…to diagnose migraine and assess the validity of the migraine diagnosis from the survey responses. The diagnostic sensitivity and specificity of our survey were 92.6% and 94.8%, respectively, with a kappa coefficient of 0.875 21 . Non-migraine headache was defined as any headache not fulfilling the migraine diagnostic criteria.…”
Section: Methodsmentioning
confidence: 60%
“…Fifth, this study used a self-reported, web-based questionnaire to assess coffee intake, headache diagnosis, insomnia, psychological status, and other relevant factors. The questionnaire used to diagnose migraine had high sensitivity and specificity 21 . Insomnia and psychological status were assessed using questionnaires with high validity and reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of pain and associated symptoms were less likely to be captured compared with those of migraine. Previous studies that reported high sensitivity in TTH screening [14,20,22] developed questions for determining pain severity to identify this disorder. However, in our study, we excluded questions for determining pain severity.…”
Section: Discussionmentioning
confidence: 99%
“…Countries are developing such screening tools in their respective languages [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Conducting studies using screening tools is inexpensive and easy, allowing for the expansion of epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Headache calendars are highly valuable and necessary tools in monitoring headache changes in frequency and type and are recommended for headache management [ 2 , 3 ]. Diagnostic headache diaries are useful in the diagnosing of primary headache disorders [ 4 ] and have been previously validated in various studies for diagnosing migraine and tension-type headache (TTH) [ 5 , 6 , 7 , 8 ]. In the long-term management of preventive treatment in patients diagnosed with a primary headache disorder, a headache calendar is recommended, if patients have learned to distinguish between different headaches [ 2 ].…”
Section: Introductionmentioning
confidence: 99%